Невизначений строк як воля сторін при укладенні договору найму (оренди) - Труфанова, Юлія; Trufanova, Yu. (ТНЕУ, 2018)
Розкрито особливості укладання договору найму (оренди) на невизначений строк. Підтримано пози- цію, що використання у тексті договору найму поняття «невизначений строк» аж ніяк не слід розцінювати як неузгодженість волі сторін стосовно строку найму. The peculiarities of concluding an indefinite lease (rent) agreement are disclosed. The notion is supported, stating the use of the «indefinite period» in the body of the agreement is not to be regarded as a misunderstanding between the desires of the parties in relation to the term of lease.
Indefinite period as the will of paties in concluding the lease (rent) agreement
Keywords: договір найму (оренди); істотна умова; строк дії договору; невизначений строк; lease (rent) agreement; fundamental condition; duration of the agreement; indefinite period